Effect of red beet flour substitution on iron content and acceptability of functional muffins: an experimental study for anemia prevention - Yeni Tutu Rohimah; Dwi Retna Prihati; Titik Lestari (Intelektual Pustaka Media Utama, 2026)
Iron deficiency anemia (IDA) remains a critical global public health burden, affecting approximately 1.8 billion people worldwide, disproportionately impacting children under five and women of reproductive age in developing countries. Conventional iron supplementation often suffers from low compliance due to gastrointestinal side effects. Thus, food-based interventions utilizing widely accepted bakery products represent a sustainable and culturally appropriate strategy for addressing micronutrient deficiencies. A completely randomized design with five red beet flour proportions(0-40%). In muffin formulations was employed, analyzing proximate, physicochemical, antioxidant, and sensory parameters were analyzed across three replications. Results: increasing red beet flour significantly (p < 0.05) enhanced Fe content (1.42-5.06 mg/100 g), total betalains, total phenolics, and antioxidant activity. Treatment T2 (20%) demonstrated an optimal balance between functional properties and sensory acceptability. The T2 formulation can contribute approximately 28% of the recommended dietary allowance for iron per serving, positioning it as a viable functional food for community nutrition interventions. This product could be integrated into supplementary feeding programs targeting vulnerable populations prone to anemia. The food-based approach offers superior compliance and sustainability compared to conventional tablet supplementation, thereby strengthening population-level strategies for IDA prevention.